Monitoring of Rice Transcriptional Responses to Contrasted Colonizing Patterns of Phytobeneficial Burkholderia s.l. Reveals a Temporal Shift in JA Systemic Response - King, Eoghan; Wallner, Adrian; Rimbault, Isabelle; Barrachina, Célia; Klonowska, Agnieszka; Moulin, Lionel; Czernic, Pierre (Frontiers in Plant Science, 2019)
In the context of plant-pathogen and plant-mutualist interactions, the underlying molecular bases associated with host colonization have been extensively studied. However, it is not the case for non-mutualistic beneficial interactions or associative symbiosis with plants. Particularly, little is known about the transcriptional regulations associated with the immune tolerance of plants towards beneficial microbes. In this context, the study of the Burkholderia-rice model is very promising to describe the molecular mechanisms involved in associative symbiosis. Indeed, several species of the Burkholderia sensu lato (s.l.) genus can colonize rice tissues and have beneficial effects; particularly two species have been thoroughly studied: Burkholderia vietnamiensis and Paraburkholderia kururiensis. This study aims at comparing the interaction of these species with rice and especially to identify common or specific plant responses. Therefore, we analyzed root colonization of the rice cultivar Nipponbare using DsRed tagged bacterial strains and produced the transcriptomes of both roots and leaves seven days after root inoculation. This led us to the identification of a co-expression jasmonic acid (JA) related network exhibiting opposite regulation in response to the two strains in the leaves of inoculated plants. We then monitored by qPCR the expression of JA-related genes during time course colonization by each strain. Our results reveal a temporal shift in this JA systemic response, which can be related to different colonization strategies of both strains.